PENTINGNYA PENDIDIKAN KEWARGANEGARAAN TERHADAP PENINGKATAN KESADARAN HUKUM MASYARAKAT INDONESIA - Syamsuri, Andi Santri; Rukman, Auliah Andika; Anggraeni, Andi Fatmawati (RESTORATIVE JOURNAL, 2024)
Citizenship Education (PKn) has an important role in increasing the legal awareness of Indonesian society. Legal awareness is a fundamental element in creating an orderly social life, minimizing legal violations, and fostering an attitude of responsibility as a citizen. Through Civics, people can understand their rights and obligations, recognize applicable norms and rules, and develop attitudes that are oriented towards compliance with the law. Apart from that, Civics also plays a role in instilling democratic values, strengthening critical attitudes, and encouraging active community participation in state life. The research method used is library research with a qualitative approach with descriptive analysis methods. Qualitative Therefore, effective citizenship education needs to continue to be developed in order to form a society that is legally aware, disciplined and responsible in carrying out its rights and obligations as citizens.Factors that influence the legal awareness of Indonesian society, especially the younger generation in Citizenship Education, such as; First, the national defense (Citizenship) education curriculum: A good curriculum will provide more applicable and contextual legal learning, so that students can understand law not only as theory but also in the practice of everyday life. Second, social media and mass media: Social media and mass media also play a role in shaping public opinion and legal awareness, both positively and negatively.